Development of Participatory Administration Model in Education Institution to Develop the Student with Special Needs of Nong Phok Municipality Kindergarten, Nong Phok District, Roi Et Province - Thipsanook, Kunyapha (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2020)
The objectives of the research article were 1) to analyze basic data in development of participatory administration model in education institution to develop the student with special needs, 2) to design and create participatory administration model in education institution to develop the student with special needs, 3) to test participatory administration model in education institution to develop the student with special needs, 4) to evaluate test result of participatory administration model in education institution to develop the student with special needs of Nong Phok Municipality Kindergarten, Nong Phok district, Roi Et province. A population or target consisted of 16 teachers, 5 students with special needs, and 5 parents of students with special needs. The research instruments were the interview, group discussion (focused group discussion), satisfaction questionnaire, mathematics and Thai language competency test, and behavior assessment in study. The data analysis used percentage, mean, standard deviation, and content analysis. The study found that: 1. The condition of the institution administration has no obvious participatory model with whom involved and the quality development of students with special needs is necessary to have innovation, methods, or suitable model to develop mathematics and Thai language skills including learning behavior of students. 2. The participatory administration model in education institution to develop the student with special needs of Nong Phok Municipality Kindergarten, Nong Phok district, Roi Et province used the model called “PU-PA Model”. 3. For the model testing of participatory administration model in education institution to develop the student with special needs of Nong Phok Municipality Kindergarten, Nong Phok district, Roi Et province, Overall learning behavior of students with special needs were at high level. 4. The teachers and parents satisfied with participatory administration model in education institution to develop the student with special needs at the highest level.